Supporting agricultural extension towards Climate-Smart Agriculture An overview of existing tools - Sala, Simone; Rossi, Federica; David, Soniia (Food and Agriculture Organization of the United Nations, 2016)
Ensuring that agriculture becomes climate smart is a priority for addressing the need for adequate, nutritionally balanced food for a growing and more demanding population in a situation of resource limitations, and climate change and variability. Despite the recognized importance of Climate-Smart Agriculture (CSA) by the Global Alliance for Climate Smart Agriculture (GASCA) and a range of international and national initiatives, the dissemination and uptake of climate smart technologies, tools and practices is still largely an ongoing, challenging process. Barriers at different levels must be overcome in all countries and solutions to these challenges must respond to specific local needs.